2021
DOI: 10.21203/rs.3.rs-549787/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Carbon Substrate Catabolism Pattern and Functional Metabolic Pathway for Microbiota of Limestone Caves

Abstract: Microbially induced calcium carbonate precipitation (MICP), a widespread biochemical process involving heterotopic bacterial communities, generally occurs in organic matter-rich environments. Limestone caves, whose oligotrophic conditions result from the absence of sunlight, are considered an extreme environment. In such environments, bacteria have the potential to form calcium carbonate. In this study, the microbial community diversity and taxonomical structure outside and inside a limestone cave was investig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…www.nature.com/scientificreports/ Functional analysis of the cmDNA. Predictive functional analysis from 16 s rRNA profiling is becoming a common tool to link the abundance of specific taxa with metabolic profiles [45][46][47] . To further explore the distinctive traits that distinguish the circulating microbiome of mussels at different sites, we studied its functional content predicted from the KEGG database using Piphillin tool.…”
Section: Site-dependent Alpha Diversity Analysismentioning
confidence: 99%
“…www.nature.com/scientificreports/ Functional analysis of the cmDNA. Predictive functional analysis from 16 s rRNA profiling is becoming a common tool to link the abundance of specific taxa with metabolic profiles [45][46][47] . To further explore the distinctive traits that distinguish the circulating microbiome of mussels at different sites, we studied its functional content predicted from the KEGG database using Piphillin tool.…”
Section: Site-dependent Alpha Diversity Analysismentioning
confidence: 99%
“…Usually, if there are no inhibitory factors that could suppress the growth and metabolic activity of bacteria the curve of AWCD keeps a typical sigmoid shape (Stefanowicz, 2006, Lima et al, 2015. However, either depending on the analysed samples and the participating species a longer lag phase (Koner et al, 2021) or specific differences in the trend can also be observed (Li et al, 2012). The Biolog EcoPlate substrates are organized in three sets that can be summarized in six guilds (amino acids, carbohydrates, carboxylic acids, amines, polymers, and phenolic compounds) and calculation of AWCD separately per each guild provided a more detailed information about utilisation of specific compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Predictive functional analysis from 16S rRNA profiling of cmDNA is routinely used to link the abundance of specific taxa with metabolic profiles [52][53][54]. To further explore the distinctive traits between sedentary and migratory S. trutta, we studied the functional content of the blood microbiome predicted from the KEGG database using the Piphillin tool (http://secondgenome.com/Piphillin) [53].…”
Section: Functional Analysis Of the Cmdnamentioning
confidence: 99%